2004
DOI: 10.1007/s11106-004-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Dodecaboride-based cutting material

Abstract: 621.785;621.9.825.7 Samples of zirconium dodecaboride are obtained by means of arc and induction melting of a mixture of zirconium and boron powders. A solder for binding the zirconium dodecaboride to the steel holder of the tool is selected. It is established that cutting tools supplied with zirconium dodecaboride may be used in operations of finish turning of adhesive-active titanium alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Low frequency region of the spectrum is characterized by a broad strong peak centered at 225 cm −1 , with a shoulder at 270 cm −1 , tentatively assigned to a motion of the metal atoms in the dodecaboride structure [15,22]. These low intensity modes are probably due to the preferential excitation in the distorted surface region, where the selection rules are more or less lifted [13,18]. In fact, the penetration depth of the exiting laser source decreases by drops off the excitation energy and, in these circumstances, the He:Ne laser source used in this experiment, (energy radiation of 1.963 eV), preferably excite the distorted surface region [15] of the target.…”
Section: Target and Films Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Low frequency region of the spectrum is characterized by a broad strong peak centered at 225 cm −1 , with a shoulder at 270 cm −1 , tentatively assigned to a motion of the metal atoms in the dodecaboride structure [15,22]. These low intensity modes are probably due to the preferential excitation in the distorted surface region, where the selection rules are more or less lifted [13,18]. In fact, the penetration depth of the exiting laser source decreases by drops off the excitation energy and, in these circumstances, the He:Ne laser source used in this experiment, (energy radiation of 1.963 eV), preferably excite the distorted surface region [15] of the target.…”
Section: Target and Films Analysismentioning
confidence: 95%
“…This involves, first, the excitation of material thin layer electrons by laser photon absorption, then material lattice relaxation by electron-phonon coupling, and finally the plasma formation [12]. Among metal transition borides, zirconium dodecaboride (ZrB 12 ) shows a wide range of interesting properties such as superconductivity at relatively high temperature and high hardness [13,14]. ZrB 12 crystal adopts the UB 12 type of structure, with very rigid boron cages and relatively weakly bonded metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…As the focus of this review is toward the applications of boride materials, we direct the reader to more detailed reviews on the nature of superhard materials. [2] The current uses of hard borides have been largely limited to machining, [332] but the high wear resistance afforded by borides may lead to other applications, such as prosthetics. [333] Applying a hard coating to mating surfaces will extend the lifetime of a prosthetic joint, reducing the need for further surgery, thus avoiding additional complications.…”
Section: Hard and Superhard Materialsmentioning
confidence: 99%
“…[188,189,279,280,383] For the synthesis of polycrystalline samples, the most common technique used is arc-melting of pressed metal and boron powders of appropriate stoichiometry on top of a copper water-cooled hearth in an inert atmosphere of argon or helium. The successful synthesis of metal borides using powders of pure metals and amorphous or crystalline boron via arc-melting includes such classes of borides as: 1) Lower metal borides and their alloys, e.g., TiB; [122] W 1−x Ta x B; [293] [51,268] and ZrB 12 ; [268,332] 4) β-rhombohedral boron [311] and its transition metal doping phases (HfB 50 , ScB 50 ); [50,55] and 5) YPtB 50 ; [388] Another common boride synthesis technique is hot-pressing of mixtures of transition metal and boron powders; using this method boride tools can also be readily made. [56,130,389] In addition this technique can be used to make metal boride composites with other compounds, such as a TiB 2 -B 4 C composite.…”
Section: ) Carbothermal Reduction (Reduction Of Metal Oxides and Bormentioning
confidence: 99%
“…11 ZrB 12 shows a wide range of interesting properties such as superconductivity with a relatively high temperature and high hardness. 12,13 ZrB 2 is an ultra-high temperature ceramic with a melting point of 3246 1C, and also possesses a high hardness of 29 GPa 14 and good high temperature strength, making it a good candidate for high temperature aerospace applications such as hypersonic flight or rocket propulsion systems. The obtained results indicated that they are all hard materials.…”
Section: Introductionmentioning
confidence: 99%